Freshwater caridean culture - Valenti, Wagner C. [UNESP]; Flickinger, Dallas L. [UNESP] (Oxford University Press (OUP), 2021)
This chapter focuses on advances in the farm production of the freshwater prawns (FWPs) Macrobrachium spp., primarily on M. rosenbergii. Farming FWPs is generally divided into four phases: reproduction, hatchery, nursery, and grow-out. The broodstock is held in earthen ponds or indoor tanks filled with freshwater. The hatchery is usually performed in intensive systems, using indoor tanks and brackish water, whereas the nursery phase uses freshwater in indoor tanks or in earthen ponds. The grow-out is generally performed in semi-intensive systems, using freshwater earthen ponds in monoculture, but integrated systems with fish, crabs, or rice are also very common. The production strategy is site specific and should be set up according to the species raised, climate characteristics, and the desired market size of the prawn. Productivity generally ranges from 1, 000 to 4, 500 kg/ha/yr, but may surpass 11, 000 kg/ha/yr in tropical areas. Production is concentrated in Asia, mainly in China. Most production is traded in local markets, and FWPs are usually sold alive, but some countries, such as Bangladesh, India, and Thailand, export frozen prawns to Europe and the USA. Substantial scientific literature and more than 100 patents support the technology for farming FWPs. However, genetics, nutrition, and interaction with other species in integrated culture are still issues. The culture of FWPs has been described in detail in a number of international review papers, books and book chapters, and practical manuals. This chapter summarizes and updates the information found in those publications.
Keywords: Aquaculture technology; Culture techniques; Freshwater prawns; Frozen prawns; Macrobrachium rosenbergii; Prawn aquaculture; Prawn monoculture